The Effect Of Empty Fruit Bunch Composting Duration And Npk Fertilizer On Oil Palm Seedling Planting Media (Elaeis Guineensis Jacq) in Nursery - Pratama, Andika; Nadhira, Ahmad; Angkat, Nina Unzila (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2025)
The purpose of this study was to determine the growth of oil palm plants by giving empty bunch and NPK. This research was carried out in the people's garden in Binjai City, North Sumatra from January to April 2024. The research used a Factorial Randomized Group Design (RAK) with 2 treatment factors, the first factor of empty bunch consisted of 3 treatment levels, namely T0 = No empty bunch (Only Topsoil), T1 = 50% Topsoil and 50% empty bunch fermentation 2 Weeks, T2 = 50% Topsoil and 50% empty bunch fermentation 4 Weeks. The second factor is NPK with three treatment levels, namely N0 = 0 ml, N1 = 15 ml, and N2 = 25 ml. The parameters observed were stem diameter (mm), plant height (cm), leaf area (cm2), and number of leaves (strands). In this study, empty bunch treatment only had a significant effect on the growth of the number of leaves, and had no significant effect on the growth of stem diameter, plant height, and leaf area. NPK treatment only significantly affects the growth of stem diameter, but does not significantly affect the growth of plant height, leaf area, and number of leaves. The interaction between empty bunch and NPK treatments had no significant effect on the growth of stem diameter, plant height, leaf area, and number of leaves.